2013
DOI: 10.1007/s12105-013-0483-7
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Chondrosarcoma

Abstract: Laryngeal chondrosarcoma is a rare tumor requiring clinical, histologic, and radiographic correlation for definitive diagnosis. Although it typically presents with low-grade histology, even high-grade histology has a fairly indolent progression in this location, with a relatively low-likelihood for metastatic potential or recurrence. Because of this, conservative surgical excision with negative margins is recommended. We present a case of a laryngeal chondrosarcoma arising from the cricoid cartilage in a patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…These tumors are often slow growing, have low metastatic potential, and tend to present with locally obstructive symptoms, such as dyspnea and dysphagia. Conservative surgical intervention is the most common modality of treatment according to case reports and a population‐based study . In our analysis of 284 hard tissue sarcomas, almost all were exclusively treated with surgery alone (70.8%), with only a small minority receiving RT, CT, or CRT (0.0%–7.0%).…”
Section: Discussionmentioning
confidence: 92%
“…These tumors are often slow growing, have low metastatic potential, and tend to present with locally obstructive symptoms, such as dyspnea and dysphagia. Conservative surgical intervention is the most common modality of treatment according to case reports and a population‐based study . In our analysis of 284 hard tissue sarcomas, almost all were exclusively treated with surgery alone (70.8%), with only a small minority receiving RT, CT, or CRT (0.0%–7.0%).…”
Section: Discussionmentioning
confidence: 92%
“…Considering the natural history, conservative surgery has been the preferred surgical option for LCS in recent years. [ 9 , 18 , 19 ] Rather than total laryngectomy, the surgical methods such as CO 2 laser resection, hemicricoidectomy, or hemilaryngectomy are the treatment of choice for low-grade LCS. Conservative surgery can preserve the structural and functional integrity of the larynx, which is very important for patient quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CT scans document even minimal deposits of calcifications, which cannot be detected on conventional radiographs (5,3). This patient's pre-operative CT scan revealed an expansive mass of 6.0×5.0 cm in the posterior area of the left thyroid cartilage lamina without gross inflation or cortical breakage (Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…Chondrosarcoma of the larynx is also uncommon, comprising only 1% of laryngeal malignancies (1), of which approximately 20% arise from the thyroid cartilage, the second most common site after the posterior lamina of the cricoid cartilage (2). The pathogenesis of chondrosarcoma of the thyroid cartilage is unknown, although a recent review suggested that several precipitating factors, such as multiple hereditary exostoses, Ollier's disease, chondromyxoid fibroma, and previous irradiation may contribute to its tumorigenesis (3). However, almost all reported cases originate from Europe or America.…”
Section: Introductionmentioning
confidence: 99%